(untitled) (Journal of The Colloquium for Information Systems Security Education, 2019)
The rise of mobile computing devices has resulted in an increased emphasis on mobile application development courses within computing curricula. While there are many available teaching modules for app development, there is a dearth of materials that incorporate secure software development for mobile devices. The goal of this project is to develop teaching modules that highlight the need for security in app development. These modules are based on CERT Java secure coding rules applicable to developing Android applications published by the Software Engineering Institute at Carnegie Melon University. This paper describes the modules we developed/are developing. These modules are further development and extension of a set of hands-on labs developed and assessed in two courses in the Spring 2017 semester. The assessment results is also discussed. These modules can be adopted by instructors of Android application development.